Efektifitas Pemberdayaan Pendamping Cegah Stunting dengan Pendekatan Interprofessional Collaboration Terhadap Status Gizi Baduta Berisiko Stunting - Sri Mulyanti; Athanasia Budi Astuti; Diyono Diyono (PT Nuansa Fajar Cemerlang, 2025)
Background. The prevalence of stunting globally in 2023 still reaches 22.3%. The prevalence of stunting in Indonesia is lower at 21.6%, but still exceeds the normal limit from WHO. The government's efforts to reduce stunting are still sectoral and have not prioritized collaboration between health professions, so the results are not optimal. This study seeks to find a new method of reducing stunting with the Interprofessional Collaboration approach. Objective. Analyzing the effectiveness of empowering Stunting Prevention Companions with an Interprofessional Collaboration Approach to the Nutritional Status of children under two years old at Risk of Stunting. Methods. A quasi experimental Pre Post control design. Conducted on 344 mothers or families who have babies aged 6-23 months at risk of stunting in Klaten Regency. Data were analyzed using the Mann Whitney Test. Results. Z Score value of pre-control group-1.13±1.25; Med:-1.13, post -1.08±1.05; Med:1.25, while the intervention group pre -0.34±1.89; Med:-1.50 and post -0.89±1.0; Med:-1.00,Mann Whitney test results Z value: -2.20, p=0.027 Conclusion. Empowerment of Stunting Prevention Companions (PECIS) with an Interprofessional Collaboration Approach effectively improves the nutritional status of toddlers at risk of stunting